Rancang Bangun Aplikasi Persediaan Barang pada Toko Endo Tani - Arianto , Adji; Amalia, Dita Rizki; Dana, Raditya Danar; Ajiz, Abul; Hamonangan, Ryan (LPPM UNIKA Santo Thomas Medan, 2022)
ABSTRACT - In this modern era, technology is developing rapidly in various aspects of life, where technology that is already known for its effectiveness has also begun to be widely used both from the education sector, government, and in the trade sector. Endo Tani shop is a type of trading business that sells various types of agricultural fertilizers, which is located at Jl. Parakan - Trajaya Blok Rabu RT/RW 004/005 Parakan Leuwimunding Village. As for the problems that exist at the Endo Tani Store, the data processing of incoming goods and outgoing goods is still using a manual system, namely by writing in books or on paper that has been provided, the data search process becomes constrained and inefficient because they have to search first in the document. This is of course less effective and efficient, considering that paper bags can be damaged or lost, which allows inventory data to be lost. Therefore, there is a need for a solution to these problems, namely designing a computerized inventory system. In the process of collecting data with the aim of solving problems, the authors use primary data sources, namely (Observation and Interview). The software methodology used for development is the prototype method, this inventory system is built using the PHP (Hypertext Preprocessor) programming language and the data is stored in a MySQL database. The final result obtained in this study is an inventory application that is expected to help and facilitate shop owners in processing goods data, searching for goods, and being able to produce the information and reports needed quickly, precisely, and accurately.